2017
DOI: 10.1016/j.maturitas.2016.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Vasomotor symptoms and metabolic syndrome

Abstract: a b s t r a c tA vast majority of menopausal women suffer from vasomotor symptoms, such as hot flushes and night sweats, the mean duration of which may be up to 7-10 years. In addition to a decreased quality of life, vasomotor symptoms may have an impact on overall health. Vasomotor symptoms are associated with overactivity of the sympathetic nervous system, and sympathetic overdrive in turn is associated with metabolic syndrome, which is a known risk factor for cardiovascular disease. Menopausal hot flushes h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 52 publications
0
21
0
4
Order By: Relevance
“…Elevated plasma leptin levels may drive sympathetic activation and dampen insulin sensitivity in obesity (Seravalle & Grassi, 2016). Other components of cardiorenal metabolic syndrome may also contribute to increased sympathetic tone as evidenced by sympathetic activation with hypertension (Seravalle & Grassi, 2016; Tuomikoski & Savolainen-Peltonen, 2017). Not surprisingly, heightened sympathetic tone is responsible for a number of unfavorable cardiorenal metabolic responses (Mahu & Domingos, 2017; Seravalle & Grassi, 2016; Tuomikoski & Savolainen-Peltonen, 2017).…”
Section: Pathophysiology Of the Cardiorenal Metabolic Syndromementioning
confidence: 99%
“…Elevated plasma leptin levels may drive sympathetic activation and dampen insulin sensitivity in obesity (Seravalle & Grassi, 2016). Other components of cardiorenal metabolic syndrome may also contribute to increased sympathetic tone as evidenced by sympathetic activation with hypertension (Seravalle & Grassi, 2016; Tuomikoski & Savolainen-Peltonen, 2017). Not surprisingly, heightened sympathetic tone is responsible for a number of unfavorable cardiorenal metabolic responses (Mahu & Domingos, 2017; Seravalle & Grassi, 2016; Tuomikoski & Savolainen-Peltonen, 2017).…”
Section: Pathophysiology Of the Cardiorenal Metabolic Syndromementioning
confidence: 99%
“…Adiponectin influences, among others, on the levels of interleukin 6 (proinflammatory cytokine), tumor necrosis factor-alpha (regulator of insulin resistance), leptin (regulator of energy balance and suppressor of food intake), and angiotensinogen PAI-1 (regulator of blood pressure and fluid balance) [175]. It was demonstrated that altered concentration of adiponectin changes the glucose homeostasis, the insulin resistance, and the enhanced inflammatory processes [176, 177]. Therefore, maintaining the stable level of adiponectin is important in the prevention of metabolic disorders like obesity [178], diabetes type 2 [179], hypertension, and cardiovascular diseases [180, 181].…”
Section: Training-evoked Increase In the Bdnf Level Prevents Symptmentioning
confidence: 99%
“…Helena Proni Fonseca Saú 1 Ana Carolina Basso Schmitt 2 Maria Regina Alves Cardoso 3 José Mendes Aldrighi 4…”
Section: Prevalence Of Hot Flashes In Women Of 40 To 65 Years Of Age mentioning
confidence: 99%